Enhancing Scientific Creativity of Prospective Physics Teachers through Guided-Inquiry-Based Electricity and Magnetism Materials with Blended Learning - Nisrina, Nina; Verawati, Ni Nyoman Sri Putu; Hikmawati, Hikmawati (Lensa: Jurnal Kependidikan Fisika, 2025)
Scientific creativity is an essential competence that must be possessed by prospective physics teachers to face the challenges of 21st-century learning. To foster this ability, innovation in learning strategies and the development of relevant and contextual teaching materials are required. This study aims to develop thematic teaching materials on electricity and magnetism based on Guided Inquiry, integrated with a Blended Learning approach to enhance the scientific creativity of physics education students. The designed learning model combines the advantages of the guided inquiry approach in exploring physics concepts with the flexibility of an online learning environment. This study uses a quasi-experimental design with a one-group pretest-posttest approach. The scientific creativity measurement instrument includes eight main indicators: originality, fluency, flexibility, elaboration, problem sensitivity, scientific imagination, hypothesis formulation, and experiment design. The analysis results show that the normalized gain (N-gain) scores for all indicators fall within the moderate to high categories, indicating a significant improvement after the implementation of the teaching materials. The novelty of this study lies in the integration of the Guided Inquiry strategy with the Blended Learning approach in developing electricity-magnet teaching materials, which has been proven effective in promoting the growth of scientific creativity among prospective physics teachers.